2020
DOI: 10.1136/bjophthalmol-2019-315187
|View full text |Cite
|
Sign up to set email alerts
|

Binocular superior visual field areas associated with driving self-regulation in patients with primary open-angle glaucoma

Abstract: Background/aimsThe aim of our study was to investigate the associations between driving self-regulation and glaucoma severity, and between driving self-regulation and glaucomatous visual field (VF) defect patterns.MethodsIn 247 patients with primary open-angle glaucoma included in this prospective observational study, a battery of ophthalmic examination was performed, including visual acuity (VA) and VF. Integrated binocular VF was constructed and mean of total deviation (mTD) values in four sectors was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The significance of the affected subfields on visual disability and daily activities in glaucoma patients are well recognized. 33,[38][39][40][41][42][43] Loss of vision in the inferior hemifield is associated with difficulties in walking down stairs, falls, fallrelated injuries, and worse physical function and thus have a greater impact on the ability to perform general daily activities. 33,40,41 Yuki et al 40 have shown that VF damage in the inferior peripheral area is related to fear of falling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significance of the affected subfields on visual disability and daily activities in glaucoma patients are well recognized. 33,[38][39][40][41][42][43] Loss of vision in the inferior hemifield is associated with difficulties in walking down stairs, falls, fallrelated injuries, and worse physical function and thus have a greater impact on the ability to perform general daily activities. 33,40,41 Yuki et al 40 have shown that VF damage in the inferior peripheral area is related to fear of falling.…”
Section: Discussionmentioning
confidence: 99%
“…Yuki et al40 have shown that VF damage in the inferior peripheral area is related to fear of falling. Moreover, superior hemifield vision is more important for near activities that require close-up vision and for driving ability 38,42,43. Yamasaki et al43 recently reported that VF deterioration in the superior periphery was associated with avoidance of driving at night and in rain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation